Effect of Deposition Time on the Morphological Features and Structure of DLC Coatings on Aluminuim-T6 by PACVD - seyed mohammad mahdi shafiei; Hamed raeiesifard; kameleh Jafari (International Journal of Advanced Design and Manufacturing Technology, 2023)
Diamond like Carbon (DLC) was deposited on aluminum substrate using Plasma Assisted Chemical Vapor Deposition (PACVD) route. Spattering, the surface was activated before deposition for increasing adhesion. Deposition time was varied from 60 minutes to 5 hours. Deposit was characterized using with grazing incidence X-ray diffraction and atomic force microscope. The mechanical property was measured using microhardness and roughness tester. The analysis showed that the deposit consisted of columnar growth of submicron and micron meter scale. Compared to substrate material, deposit showed higher hardness and roughness. These results show that growth of DLC layer includes three stages. The first stage is primary growth of nuclei, and then these nuclei join together in second stage. In third stage, secondary growth of these nuclei happens.